Exploring the potential of PPP in Philippine irrigation - Inocencio, Arlene B. (Animo Repository, 2018)
© 2018 by De La Salle University. Irrigation systems in many Asian countries including the Philippines remain heavily dependent on public funds and are mostly unsustainable. Systematic degradation due to poor and inadequate management, maintenance and operation, and limited public funding calls for a new approach. Governments have implemented participatory irrigation management, which evolved into an irrigation management transfer (IMT). While progress has been slow, the IMT appear to present some improvements in the irrigation sector. However, the lack of incentives and motivation for irrigators associations (IAs) to become autonomous and irrigation agencies’ unwillingness to let go further slows the growth of the irrigation sector. For the irrigation sector to grow fast and to provide the right incentives and policy environment for both farmers and IAs in the Philippines, the next logical step to take is a public-private partnership (PPP) between the responsible public agency and IAs. This paper explores the potential of establishing a PPP by empowering existing IAs beyond the IMT to become viable and sustainable private companies. This paper proposes four financial options for the irrigators associations-irrigation service management company (IAs-ISMC) to become more independent from public subsidies. These financial options are defined, which include doing community work beyond the PPP contracts to generate additional funds to the irrigation service fees (ISF). Necessary policy measures and institutional arrangements are proposed to enable the establishment of a start-up private company.